A framework for critical thinking in process safety management. Issue 4 (11th October 2016) - Baybutt, Paul
Abstract : Process safety management requires many decisions to be made that influence the safety of processes. Human decision making is subject to flaws in reasoning and poor decisions have led to process safety incidents. The discipline of critical thinking can be used to evaluate the merits of decisions. Its application in process safety management will reduce the likelihood of incidents. A framework for applying critical thinking is described and its use is illustrated with a worked example. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 337–340, 2016